On Some Properties of Metric F-Structure Satisfying F^2k+1+F=0 - Lakhan Singh; Shailendra Kumar Gautam (International Journal of Mathematics And its Applications, 2017)
In this paper, we have studied various properties of the F-structure satisfying F^2k+1+F=0. Where k is positive integer The metric F- structure, f induced on each integral manifold of tangent bundle l^* have also been discussed.